EMPIRICAL EVALUATION OF DEPENDABILITY OF AVIONICS COMPONENTS UNDER CONDITIONS OF AFTER-SALES SERVICE - Gribov, Victor; Hryshchenko, Yurii V.; Hryshchenko, Yurii Yu. (Proceedings of National Aviation University (archive), 2018)
Purpose: the main purpose of this research is to improve the accuracy of dependability evaluation of avionics components under conditions of after-sales service. The accuracy of calculation of reliability measures offered to improve by the application of probabilistic-physical diffusion nonmonotonic failure model. Methods: the article proposes technique for estimating the accuracy of the quantile method based on the simulation modeling of the process of occurrence of single failures, confirming the high data validity of the empirical estimates of mean time to failure. Results: we obtained the quantitative assessment of evaluation errors of mean time to failure. The calculation was made for practically important in the operation of onboard equipment ranges of variation of first failure in the conjunction of the total number of sets of the same type operated. The presented results of the research show that the quantile method is effective tool for estimation the actual reliability of operated avionics components by single failures. Discussion: during the operational phase of aircraft the quantiles method with using of probabilistic-physical model of failure is an effective tool for obtaining adequate estimates of dependability of maintained avionics components. First of all it concerns the mean time to failure - one of the measures of reliability. This measure is widely used in international standards. The presented methodology provides increasing the efficiency of integrated logistics support in the process of monitoring the technical condition and maintenance characteristics of aircraft components.